To rearrange the equation c = ax + by for the quantity of interest y, we need to isolate y on one side of the equation.
Given: c = ax + by
Let's start by subtracting ax from both sides of the equation:
c - ax = ax + by - ax
This simplifies to:
c - ax = by
Now, let's divide both sides of the equation by b to isolate y:
(c - ax) / b = by / b
Simplifying further:
(c - ax) / b = y
Therefore, the rearranged equation for the quantity of interest y is:
y = (c - ax) / b
rearrange the equation c = ax + by for the quantity of interest y. make sure to show your step
1 answer